Ageing in forensic psychiatric secure settings: the voice of older patients - Di Lorito, Claudio; Dening, Tom; Völlm, Birgit (Taylor & Francis, 2018)
Older patients account for around 20% of the population in secure forensic psychiatric services in the UK. However, little qualitative research has investigated the experience of ageing in secure settings. This study aimed to gather the individual views of a sample of patients over 50 years old in the UK at different levels of security. Fifteen participants were selected and underwent one-on-one qualitative interviews. The interviews were analysed through thematic analysis, which generated seven themes: Self-agency, activities, social life, practical matters, recovery, physical health and service improvement. Study findings highlighted the complexity of ageing in secure settings. Despite the positive feedback reported in aspects such as physical health care, education opportunities, staff and support of religious practices, participants experienced added barriers to recovery, caused by social isolation/withdrawal and activities/treatment that did not respond to their complex age-related needs, generating poor motivation to engage. Our findings call for the development/implementation of programmes tailored to the unique needs of older patients. This process requires an active involvement of the primary stakeholders and further patient-centred research.